Ecogeographical classification of Arctic vegetation based on shoots density determinations. - Böcher, Tyge W. (Meddelelser om Grønland, 1977)
A number of Greenland vegetation stands occurring on dry or mesic soils have been investigated according to shoots density. The objective density determination method is shortly described. The stands are arranged in a number of plant communities and each stand as well as the communities are characterized ecologically and by the percentage occurrence of ten ecogeographical distributional types. These "types" are treated like lifeforms, and their occurrences are based on density values (frequency sums). The main object of the paper, however, is not description of vegetation so much as by detailed analyses of selected habitats to contribute to an elucidation of the autecology of a number of species occurring in Greenland and arctic regions.